Social Capital in Community Development Evaluation Applications to Realize Village SDGs: Study of the Commodity Transformation Program in Warjabakti Village - Atlandi, M. Hasnan; Gunawan, Wahyu; Lesmana, Aditya Candra; Nugraha, Ardi Maulana (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2025)
Community development programs cannot be separated from dynamics that can threaten the sustainability of the program. Therefore, evaluation activities are important to ensure the effectiveness of the program. Different from previous studies that focused evaluation on program structure, this study aims to focus on the actors involved and the accompanying social capital in order to build a program with a strong foundation. Robert D. Putnam's Social Capital Theory is used to analyze the network, trust, and social norms of actors in program implementation. Meanwhile, James Copestake and Richard Walker's Theory of Change is used as the basis for analyzing changes and impacts caused by the program based on input, output, outcome, and impact. This study was conducted on a community development program in Warjabakti Village which used qualitative methods to describe problems with interviews and observations as primary data. Meanwhile, literature and documentation studies were used as secondary data. Then, data validity was tested through source triangulation. The results of the study showed that the formation of a development program in Warjabakti Village with a weak social capital foundation was an input that ultimately affected the sustainability of the program which could not be sustained and even had an impact at every stage of change. This has an impact that can hinder the achievement of Village SDGs in the form of the community being closed to cooperation, especially in achieving point 8 "Equitable Village Economic Growth."